Peran Pemerintah Desa dalam Mewujudkan Good Governance Pada Pemerintah Negeri Hila Kabupaten Maluku Tengah - Pelu, Aldy; Madubun, Jusuf; Wance, Marno (Journal of Government Science Studies, 2023)
Weak public service accountability, the Hilla State Government is slow, unresponsive and lacks openness to the public. So that the implementation of good governance can provide development in aspects of service to the community. The research method used is descriptive qualitative with an in-depth interview approach. The research findings are (1). accountability, participation, law enforcement need to be a form of improvement for the development of Hilla State development. (2). Synergy, cooperation between the community, the government needs to build continuous institutional communication for future development.